Mini game design and development - Wang, Zili (2017)
This report introduces the final year project of the Serious Game which is conducted by Wang Zili using Unity3D and Leap Motion device for Wrist Exercise. It starts with introducing an actual problem which is Wrist Tendonitis in our real life followed by the technologies used to establish a serious game system that brings a fresh user experience not only for patients but also for doctors to do wrist exercises and data analysis. This report describes the details of the game design, UX design, technical design, and implementation in software engineering domain together with the testing and conclusion which includes the possible further improvement and implementation. Finally, a game gallery is attached in the end of the report.